Analyzing the natural elements of Emily Dickinson’s selected poems using eco-feminist criticism - Meem, Jannatul Atia (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2018.